Pengenalan Sariawan dan Penyuluhan Potensi Buah Nanas dalam Pencegahan Sariawan Rongga Mulut pada Peserta Open House Institut Ilmu Kesehatan Bhakti Wiyata Kediri - Sawitri Dwi Indah Pertami; Ernita Sari; Herlambang Prehananto; Eka Resti Efrata; Nikmatus Sa’adah; Rudi Irawan; Nur Dianawati; Endah Kusumastuti (Universitas 45 Surabaya, 2025)
The mouth sores are one of the most common oral lesions in adolescents, which refer to several different conditions, the most common of which are recurrent aphthous stomatitis and traumatic ulcers. Traumatic ulcers are generally caused by physical trauma such as biting while chewing, sharp foods, or improper brushing techniques. Recurrent aphthous stomatitis is idiopathic, with predisposing factors of hormones, stress, and nutritional deficiencies. Although relatively mild, canker sores can cause pain, interfere with eating and speaking activities, and reduce quality of life. Early prevention is very important, one of which is through a nutritional approach. Pineapple (Ananas comosus) contains phytochemical compounds such as bromelain, vitamin C, and antioxidants which are known to have anti-inflammatory effects and accelerate wound healing. This community service activity aims to introduce the public, especially high school students, to mouth sores, their causes, how to prevent them, and the potential of pineapple as a natural agent in preventing canker sores. The activity was carried out in the framework of the Open House of the Bhakti Wiyata Kediri Health Science Institute and was attended by 100 high school students from various public and private schools in Kediri City and its surroundings, consisting of 57 female students and 23 male students. The activity methods were in the form of counseling, presentation, and pre and post tests. The survey results showed an increase in participant knowledge from 58.2% to 92.6%. This activity was effective in increasing student awareness of mouth sores and the benefits of pineapple in maintaining oral health.